Acute safety, effectiveness, and real-world clinical usage of ultra-high density mapping for ablation of cardiac arrhythmias: results of the TRUE HD study. Issue 4 (27th February 2019) - Hindricks, Gerhard; Weiner, Stanislav; McElderry, Tom; Jaïs, Pierre; Maddox, William; Garcia-Bolao, Jose Ignacio; Yong Ji, Sang; Sacher, Frederic; Willems, Stephan; Mounsey, John; Maury, Philippe; Bollmann, Andreas; et al.
Abstract: Aims: The objective of this study was to verify acute safety, performance, and usage of a novel ultra-high density mapping system in patients undergoing ablation procedure in a real-world clinical setting. Methods and results: The TRUE HD study enrolled patients undergoing catheter ablation with mapping for all arrhythmias (excluding de novo atrial fibrillation) who were followed for 1 month. Safety was determined by collecting all serious adverse events and adverse events associated with the study devices. Performance was determined as the composite of: ability to map the arrhythmia/substrate, complete the ablation applications, arrhythmia termination (where applicable), and ablation validation. Use of mapping system in the ablation validation workflow was also evaluated. Among the 519 patients who underwent a complete (504) or attempted (15) procedure, 21 (4%) serious ablation-related complications were collected, with 3 (0.57%) potentially related to the mapping catheter. Four hundred and twenty treated patients resulted in a successful procedure confirmed by arrhythmia-specific validation techniques (83.3%; 95% confidence interval: 79.8–86.5%). A total of 1419 electroanatomical maps were created with a median acquisition time of 9:23 min per map. Of these, 372 maps in 222 (44%) patients were collected for ablation validation purposes. Following validation mapping, 162/222 (73%) patients required additional ablation. Conclusion: In the TRUE HD study mapping was associated with rates of acute success and complications consistent with previously published reports. Importantly, a low percentage of events (0.57%) was attributed to the mapping catheter. When performed, validation mapping was useful for identifying additional targets for ablation in the majority of patients.